Genome announcement: Complete genome sequence of a novel mupapillomavirus, HPV204 - Kocjan, Bostjan J. (2015)
Human papillomaviruses (HPVs) are small, non-enveloped viruses with a circular double-stranded DNA genome, etiologically associated with various benign and malignant neoplasms of the skin and mucosa. As of May 30, 2015, 201 different HPV types had been completely sequenced and officially recognized and divided into five PV-genera: Alpha-, Beta-, Gamma-, Mu-, and Nupapillomavirus. The Mupapillomavirus genus currently consists of only two HPV types: HPV1 and HPV63, identified in 1980 and 1993, respectively, both associated with sporadic cases of cutaneous warts. In this preliminary study, we announce the complete genome sequence of a novel HPV type, now officially recognized as HPV204. Based on preliminary data, the genome of HPV204 comprises a total of 7,227 bp and contains five early open reading frames (E1, E2, E4, E6, and E7) and two late ORFs (L1 and L2). No E5 ORF could be identified. Preliminary HPV204 clusters to the Mu-PV genus, species Mu-3.